Improving in-house medical waste management: a pilot research - Akter, Nasima; Ali, Miah Rahmat (BRAC Research and Evaluation Division (RED), 2020)
BRAC has undertaken a pilot project on improving in-house medical waste management in collaboration with three selected hospitals (Dhaka Shishu Hospital, Institute of Child Health and Shishu Shasthya Foundation, and one BRAC upgraded Shushastha). As an outcome of this project, a manual on in-house medical waste management has been prepared. The pilot programme was designed to build awareness/consciousness among hospital staff and initiate some action programs with the hospital staff to streamline the existing waste management systems. To make the pilot programme successful the following steps were selected: i) baseline survey, ii) manual development and training, iii) implementation and follow up, and iv) finalize the manual on in-house medical waste management. The eight-month long project was implemented during January-August 2004. Baseline survey found that, a number of hospital staff specifically nurses and cleaners had been suffering from various kinds of infectious diseases, such as hepatitis B/C, skin disease/allergy, infection, diarrhoea, fever, headache, cough, asthma, and typhoid. Nurses were mostly injured during needle breaking (42%) and ampoule breaking (34%), and cleaners were injured during handling and cleaning waste. It was found that, 60% of sold items were plastics collected by unauthorized waste pickers such as used syringes, saline bags, water bottles, etc. from hospitals. After introducing the in-house management system in three hospitals, the amount of infectious waste became around 2%, recyclable 4-6% and above 90% were general waste that could be dumped to the municipal bin without treatment. Nevertheless, it should be kept in mind that the amount and quality of waste depends on proper segregation, hospital size, services, diseases type, waste category, and seasonality. To improve the medical waste management in Bangladesh, we recommend the following: i) raising awareness, training, and capacity building of hospital staff, ii) responsibilities inside hospital (designated personnel), iii) monitoring mechanism and committee, iv) role of City Corporation (transportation and central treatment system), v) hospital initiatives for proper medical waste management (cost, return), and vi) private sector and NGOs involvement.